Pathways for Holliday junction processing during homologous recombination in Saccharomyces cerevisiae. - Ashton, T; Mankouri, H; Heidenblut, A; McHugh, P; Hickson, I (2011)
The Saccharomyces cerevisiae Rmi1 protein is a component of the highly conserved Sgs1-Top3-Rmi1 complex. Deletion of SGS1, TOP3, or RMI1 is synthetically lethal when combined with the loss of the Mus81-Mms4 or Slx1-Slx4 endonucleases, which have been implicated in Holliday junction (HJ) resolution. To investigate the causes of this synthetic lethality, we isolated a temperature-sensitive mutant of the RMI1 strain, referred to as the rmi1-1 mutant. At the restrictive temperature, this mutant phenocopies an rmi1Δ strain but behaves like the wild type at the permissive temperature. Following a transient exposure to methyl methanesulfonate, rmi1-1 mutants accumulate unprocessed homologous recombination repair (HRR) intermediates. These intermediates are slowly resolved at the restrictive temperature, revealing a redundant resolution activity when Rmi1 is impaired. This resolution depends on Mus81-Mms4 but not on either Slx1-Slx4 or another HJ resolvase, Yen1. Similar results were also observed when Top3 function was impaired. We propose that the Sgs1-Top3-Rmi1 complex constitutes the main pathway for the processing of HJ-containing HRR intermediates but that Mus81-Mms4 can also resolve these intermediates.